2002
DOI: 10.1007/s00464-001-9151-1
|View full text |Cite
|
Sign up to set email alerts
|

Early experiences of robotic surgery in children

Abstract: Compared to conventional laparoscopy, the three-dimensional high-quality vision, advanced instrument movement, and improved ergonomic position of the surgeon appear to enhance surgical precision. Robotic surgery in children using the Da Vinci system seems to be feasible and safe. However, the technique is limited due to the fact that instruments adapted to the size of small children are not available. Furthermore, the high costs and prolonged system setup are disadvantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
51
0
5

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(57 citation statements)
references
References 11 publications
1
51
0
5
Order By: Relevance
“…Previous studies have reported the safety and feasibility of robot-assisted antireflux surgery in children [1][2][3][4][5][6]. The first report on a randomised study [2] concluded that there was no obvious added benefit from the robotic technique compared with laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have reported the safety and feasibility of robot-assisted antireflux surgery in children [1][2][3][4][5][6]. The first report on a randomised study [2] concluded that there was no obvious added benefit from the robotic technique compared with laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 96%
“…The question remains if these advantages detected experimentally can be transferred to the clinical setting. In fact, several clinical studies have demonstrated the feasibility and safety of a variety of robotassisted procedures [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. However, there is only a limited number of controlled trials.…”
Section: Introductionmentioning
confidence: 99%
“…Robotic surgery technology and techniques have made rapid advances in recent years across a wide range of clinical applications including cardiovascular surgery (Kappert et al, 2000), urology (Menon, Tewari, Baize, Guillonneau, & Vallancien, 2002), pediatrics (Gutt et al, 2002), gynecology (Falcone, Goldberg, Margossian, & Stevens, 2000), neurosurgery (Giorgi, Sala, Riva, Cossu, & Eisenberg, 2000), orthopedics (Jakopec et al, 2001), microsurgery (Siemionow, Ozer, Siemionow, & Lister, 2000), and fetal surgery (Aaronson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%